PT Naruna Karya Bersama Offline Marketing Innovation In Building Relationships with Customers: Inovasi Pemasaran Offline PT Naruna Karya Bersama Dalam Membangun Hubungan Dengan Pelanggan - Angelica Br Stumeang; Rahman Amrullah Suwaidi (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
PT Naruna Karya Bersama uses new offline marketing strategies to improve direct customer relationships. Offline marketing remains relevant because it is able to build personal relationships and closeness with customers, even though digital media is increasingly dominating. The focus of this internship is to analyze various innovations of PT Naruna Karya Bersama in offline marketing, such as attending IGTKI Meetings in Kindergartens, and direct promotions to Kindergartens. Interviews with mentors in the marketing department and analysis of documentation related to offline marketing strategies and implementations were used as data collection methods. The results of the analysis show that new marketing innovations increase brand awareness, direct interaction, and loyalty. By utilizing conventional media, businesses can provide an interesting and relevant customer experience while maintaining their brand's core values. This activity also found problems in the use of offline marketing strategies, such as high costs and measuring effectiveness. The results of the activity show that PT Naruna Karya Bersama must continue to develop and adjust offline marketing strategies with market dynamics and consumer behavior.